IMF-supported programs in capital account crises - Ghosh, Atish...[et al.] (IMF WashingtonUS, 2002)
Examines the experience with IMF-supported programmes in the context of eight capital accounts in the 1990s. Focuses on the broad macroeconomic strategy of these programmes in addressing the crises viz. the financing and external adjustment envisaged and the role of macroeconomic and structural policies.